فاعلية تقنية الجمبا العقلي في تحسين مهارة الكتابة لدى تلاميذ العسر الكتابي دراسة ميدانية بمدينتي الجلفة و الأغواط - رباب حبيبة قحماني; سمية بوزيدي; سعدية زروق (My University, 2023)
This study aimed to the effectiveness of the proposed treatement program which is based on mental gymnastics technique in improving skill of students with dysgraphia . This technique was applied on 14 cases from 4th grade and 5th grade primary school pupils, in which we use the experimental method To achieve the purposes of this study, we dependon the following materiels .  Measurement of dysgraphia to Dr Ben Bouzid.  Mental gymnastics technique thorough PACE application. The following hypothesis evas also formulated : “mental gymnastics in fluences on the improvement of writing skill of students with dysgraphia” . The results of the study revealed that : “The proposed treatement program is effective in improving the writing skill in 4th and 5th grade primary school pupils. Key words: mental gymnastics, dysgraphia